2021
DOI: 10.1039/d1cy00382h
|View full text |Cite
|
Sign up to set email alerts
|

Dry reforming of methane on bimetallic Pt–Ni@CeO2catalyst: ain situDRIFTS-MS mechanistic study

Abstract: Bimetallic Pt-Ni catalysts can promote catalytic dry reforming of methane (DRM) with the improved activity and deactivtaion resistance compared to the relevant monometallic catalysts. Further development of the Pt-Ni catalyst...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Many reports have assigned the peaks of carbonaceous species. The assignment of carbonaceous species used for this study and their values in the literature are shown in ESI † 5,11,48–73 . We assigned peaks in the range of 1800–2100 cm −1 to carbonyl species adsorbed onto Pt, but they are not shown in the table.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many reports have assigned the peaks of carbonaceous species. The assignment of carbonaceous species used for this study and their values in the literature are shown in ESI † 5,11,48–73 . We assigned peaks in the range of 1800–2100 cm −1 to carbonyl species adsorbed onto Pt, but they are not shown in the table.…”
Section: Resultsmentioning
confidence: 99%
“…The assignment of carbonaceous species used for this study and their values in the literature are shown in ESI. † 5,11, We assigned peaks in the range of 1800-2100 cm À1 to carbonyl species adsorbed onto Pt, but they are not shown in the table. In this measurement, we applied the EF to the catalyst in the CO 2 ow and compared the spectra before and aer the application of EF.…”
Section: Effects Of Ef On Co 2 Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have been exerted to develop novel catalysts that can increase CO 2 and CH 4 activities at low temperatures. Nickel is the most prevalent metal-based catalyst because of its abundancy and low cost, making it suitable for industrial catalytic processes; however, Ni is rapidly deactivated because of high carbon formation from side reactions, either methane cracking or CO disproportionation [ 105 , 106 ] Noble metals, such as Pd [ 106 ], Ru, and Pt [ 107 , 108 , 109 , 110 ], are suggested to replace Ni because they are highly resistant to carbon formation. However, their expensiveness restricts their promising properties in the larger market.…”
Section: Co 2 Conversion Processes and Productsmentioning
confidence: 99%
“…Pt-based alloys and intermetallic compounds have been intensively studied because of their potential applications in magnetics 1 , electronics 2 , and particularly in catalysis 3,4,5,6,7 . Although effective, Pt is one of the most expensive catalysts.…”
Section: Toc Introductionmentioning
confidence: 99%